On the principle of the philosophical project of promoting philosophy to a “strict science” (2011)
Husserl argued that intuition is the “principle of principles” governing phenomenological research, and that it would guarantee philosophy to be raised to the level of “strict science.” This research project aims to show how phenomenology is directed towa